Three-dimensional carbon-based endogenous-exogenous MoO2 composites as high-performance negative electrode in asymmetric supercapacitors and efficient electrocatalyst for oxygen evolution reaction. Issue 4 (15th February 2023) - Zhu, Wen; Yan, Xuehua; Huang, Xinpeng; Wu, Sutang; Chen, Hao; Pan, Jianmei; Li, Tie; Shahnavaz, Zohreh
Abstract: It is not an easy way to design composite electrodes with a high concentration of the constituent. This study cleverly exploited the phase transformation of molybdenum oxide to synthesize three-dimensional carbon-based endogenous-exogenous MoO2 composites (EEC) by a two-step process. MC-15 exhibited the most outstanding electrochemical performance among EEC, with a specific capacitance up to 411.1 F g −1 in Na2 SO4, due to the design of MoO2, which could be highly loaded with three-dimensional carbon. In addition, the electrode capacitance remains up to 94.1% after 5000 cycles, attributed to the synergy effect of three-dimensional carbon and molybdenum dioxide by providing an abundance of active sites for MoO2 and overcoming its stacking. In this way, the electrochemical properties of the EEC electrode are not compromised by the volume expansion during the electrochemical process. The energy density of the asymmetric supercapacitor using this material as the negative electrode and MnO2 @CC is 14 W h kg −1 at a power density of 802 W kg −1, showing a significant increase in energy density over the asymmetric supercapacitor with a conventional negative electrode (activated carbon, energy density of 3.36 W h kg −1 and power density of 700 W kg −1 ). Its specific capacitance remained 84.9% after 2500 cycles. In addition, an overpotential of only 348 mV was required to drive oxygen evolution in alkaline electrolytes with a Tafel slope as low as 88.7 mV dec −1 ; the 20 h stability test retains almost 100%. The results show that the design optimization of the negative electrode material provides a simple and effective strategy to increase the energy density of supercapacitors, and EEC electrode materials are a great candidate to be utilized in supercapacitors with excellent performance as well as electrolytic water.